2017
DOI: 10.1016/j.bbrep.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrozymographic evaluation of the attenuation of arsenic induced degradation of hepatic SOD, catalase in an in vitro assay system by pectic polysaccharides of Momordica charantia in combination with curcumin

Abstract: Momordica charantia (MC) fruit known as bitter gourd, is of potential nutritional and medicinal value. The objectives of the present in vitro study were to evaluate the efficacy of bioactive pectic polysaccharides (CCPS) of MC along with another well-known bioactive compound curcumin in the abrogation of hepatocellular oxidative stress persuaded by sodium arsenite. Electrozymographic method was developed for the assessment of superoxide dismutase (SOD) and catalase activities of liver tissues maintained under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
(70 reference statements)
0
5
0
1
Order By: Relevance
“…The effect of “As expulsion therapy” in managing chronic As poisoning is effective but has certain limitations. Research has established that the pectic polysaccharides of Momordica charantia could inhibit the oxidative stress of liver cells induced by sodium arsenite [ 10 ]. Besides, numerous studies have demonstrated that polysaccharides regulate immunity and protect the liver [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of “As expulsion therapy” in managing chronic As poisoning is effective but has certain limitations. Research has established that the pectic polysaccharides of Momordica charantia could inhibit the oxidative stress of liver cells induced by sodium arsenite [ 10 ]. Besides, numerous studies have demonstrated that polysaccharides regulate immunity and protect the liver [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Praveen et al applied a combination of a polysaccharide from Mormodica charantia and curcumin from Curcuma longa to prevent As 3+ degradation of SOD and catalase in the liver. 107 Hepatic tissue MDA and CD levels showed that the coadministration offered better antioxidant effect compared to single applications and the highest restoration of SOD/catalase was recorded in the co-administration experiments.…”
Section: Synergistic Amelioration Of Heavy Metal-induced Diseases Usimentioning
confidence: 92%
“…MCF-7 cells treated with M. charantia during G2-M phase increased expression of p53 and p21; pChk1/2 inhibited the expression of cyclin B1 and cyclin D1 by involving regulation of cell cycle, thus inhibiting the growth of breast cancer cells [98]. Combination of M. charantia and C. domestica prevented cell damage and provided significant protection against changes in malondialdehyde (MDA), conjugated diene, and defense antioxidants [99]. Tahitian noni dietary supplements can also improve testicular toxicity supplemented with high doses of M. charantia extract [100].…”
Section: Momordica Charantiamentioning
confidence: 99%